Add-On Effect of Angiotensin Receptor Blockade (Candesartan) on Clinical Remission in Active IgA Nephropathy Patients Treated with Steroid Pulse Therapy and Tonsillectomy: a Randomized, Parallel-Group Comparison Trial - Kentaro Kohagura; Hisatomi Arima; Hitoshi Miyasato; Tung-Huei Chang; Masanobu Yamazato; Hiroyuki Kobori; Akira Nishiyama; Kunitoshi Iseki; Yusuke Ohya (Karger Publishers, 2018)
Background/Aims: Angiotensin receptor blockers (ARBs) may be beneficial for clinical remission during conventional therapy with tonsillectomy and steroid pulse (TSP) for active IgA nephropathy. Methods: Seventy-seven patients with active IgA nephropathy were randomly assigned to the control arm with conventional regimen (TSP followed by oral prednisolone) (n = 37) or the ARB arm with conventional regimen plus ARB candesartan for the first 6 months (n = 40). Patients not achieving proteinuria remission at 12 months in either arm were administered candesartan, which was titrated until the 24-month follow-up. The primary endpoints were remission of proteinuria (< 0.3 g/gCr) and hematuria at 12 months. Results: Baseline proteinuria (g/g Cr) were comparable between the control and ARB arm (1.02 vs. 0.97, P = 0.97). Similarly, cumulative remission rates at 6, 12, and 24 months were comparable between the control and ARB arms (37.8% vs. 35% [P = 0.80], 48.7% vs. 38.5% [P = 0.37], 71.4% vs. 51.3% [P = 0.08]). Proteinuria, which was slightly worse in the control arm than in the ARB arm at 6 months, was comparable afterwards (0.20 vs. 0.23 g/g Cr at 12 months; 0.12 vs. 0.13 g/g Cr at 24 months). Significant reductions observed in urinary angiotensinogen were almost comparable between the two treatment arms at both 6 and 12 months. Conclusion: Early candesartan treatment combined with TSP may not benefit clinical remission regardless of the blood pressure. ARB titration later during the treatment might provide benefit for patients with active IgA nephropathy.